A Theoretical Study of AI-Driven Socio-Economic Challenges for Generation Z from the Perspective of Nepal, and the Global South - Ojha, Rajendra (Nepalese Journal of Management Science and Research, 2026)
Artificial Intelligence (AI) is a transformative yet disruptive force in the 21st-century economy, driving innovation while exacerbating socioeconomic disparities among Generation Z in developing countries such as Nepal. Using a qualitative descriptive case study and secondary data (2011–2024), this study examines AI’s interaction with infrastructural gaps, digital illiteracy, and policy stagnation. Findings reveal that the algorithmic divide is excessively affecting Nepali youth, causing employment anxieties, unequal educational access, and systemic digital unpreparedness. The study recommends inclusive policies, targeted digital literacy programs, and infrastructure development, while introducing two mid-range theories, the Algorithmic Exclusion Cycle (AEC) and AI-Generation Disparity Theory (AGDT), to examine these context-specific challenges.